SRT2104 enhances dendritic outgrowth and spine formation through Sirtuin 1-mediated mTORC1 signaling - Mi Kyoung Seo; Jung Goo Lee; Ji Hyun Kim; Dae-Hyun Seog; Sehoon Jeong; Seong-Ho Kim; Jin Young Lee; Sung Woo Park (Scientific Reports)
Abstract Impaired neuroplasticity is a one of the key pathological mechanism of depression. Sirtuin 1 plays a crucial role in neuroplasticity; however, its precise mechanisms remain unclear. This study examined whether sirtuin 1 regulates dendritic outgrowth and spine formation via mTORC1 signaling in rat primary cortical cells under dexamethasone-induced neurotoxic conditions. Cortical cells were treated with SRT2104 (0.1, 1, and 10 µM), a selective sirtuin 1 activator, in the presence of dexamethasone (500 µM). Protein levels of sirtuin 1, mTORC1 signaling components, and synaptic markers (PSD-95 and GluA1) were analyzed by Western blotting, while dendritic outgrowth and spine density were assessed via immunofluorescence. SRT2104 significantly increased sirtuin 1 expression and ERK1/2 (a downstream target of sirtuin 1) phosphorylation. SRT2104 led to a substantial augmentation in the phosphorylation levels of mTORC1, as well as 4E-BP1 and p70S6K, which are downstream targets of mTORC1. Furthermore, SRT2104 led to an increase in dendritic outgrowth and spine density. Conversely, sirtuin 1 knockdown by siRNA transfection markedly reduced ERK1/2 and mTORC1 phosphorylation, as well as dendritic complexity and spine formation. These results suggest that sirtuin 1 promotes neuroplasticity by activating mTORC1 signaling, providing potential therapeutic implications for depression treatment.